Penyuluhan hukum terkait partisipasi masyarakat dalam proses pembentukan peraturan desa di Desa Koto Masjid Kecamatan XIII Koto Kampar Kabupaten Kampar - Dessy Artina; Mexsasai Indra; Emilda Firdaus; Gusliana HB; Zulwisman Zulwisman; Muhammad A Rauf; Zainul Akmal (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
After the enactment of Law Number 6 of 2014 concerning Villages on 15 January 2014, the Republic of Indonesia now has laws specifically regulating the administration of village governance. A very important part is the arrangement of village regulations. Village regulations are set by the village head after obtaining approval with the Village Consultative Body. In the process of establishing village regulations, community participation is needed, so that the output of village regulations can fulfil aspects of local community needs that are conveyed through the Village Consultative Body. The aspirations of the local community in the form of input and contribution ideas are more effective, because community complaints and opinions are taken into consideration in decision making. Related to this matter, the formulation of the problem in this study is how is community participation in the process of establishing Village Regulations in Koto Masjid Village, District XIII, Koto Kampar, Kampar Regency? There are still very many village organizers (Village Heads and Village Consultative Bodies) and village communities who do not yet have the knowledge and expertise in the field of legislation. This has the potential to affect the success of the implementation of the Law on Villages, and even does not rule out the possibility of creating legal chaos, among others, the occurrence of conflicts and overlapping laws and regulations. So that in the future knowledge of the establishment of legislation is needed which is able to encourage people to participate in the formation of village regulations, realize Village Regulations that are aspirational, responsive, obedient, harmonious and harmonious vertically and horizontally in the framework of developing national legal systems based on The 1945 Constitution of the Republic of Indonesia, and produced a Draft Law and Regulations that could be accounted for philosophically, juridically and sociologically. Knowledge can be obtained through legal counselling, especially legal counselling related to community participation in the process of establishing village regulations in Koto Masjid Village, District XIII Koto Kampar, Kampar District.